Hasil Belajar Kognitif Siswa Pada Topik Isomerism di Pelajaran Kimia Kelas XII SMA ABC Tangerang - Afrilia Kristiana; Antonius Lase; Celine Putri Larasati; Theresia Christy (Magister Teknologi Pendidikan Fakultas Pascasarjana Pendidikan Universitas Pelita Harapan, 2025)
Chemistry learning at the senior high school level involves abstract concepts that require higher-order thinking skills (HOTS), particularly in complex topics such as isomerism. Previous studies have shown that students often experience difficulties in mastering this material, as indicated by learning outcomes that have not yet reached the Minimum Mastery Criteria (KKM). To further investigate this issue, an additional assessment was conducted in the form of a cognitive test. This study aims to determine the average cognitive learning outcomes of students on the topic of isomerism and to analyze the effect of higher-order thinking skills on these outcomes. A quantitative research design was employed using a test instrument consisting of ten multiple-choice questions administered to 36 twelfth-grade students at SMA ABC Tangerang. The validity and reliability of the instrument were examined through correlation analysis and Cronbach’s alpha, confirming that the test items were valid and reliable. Data were analyzed using normality tests, mean comparison tests, and simple linear regression. The findings indicated that the average cognitive learning outcome exceeded the KKM score of 60, as demonstrated by tH (2.76) > tT (1.69), with normally distributed data. Moreover, the regression results showed a significant influence of HOTS on students’ learning outcomes, as evidenced by Fcal (53.68) > Ftable (4.15). Overall, the study concludes that higher-order thinking skills play a crucial role in students’ success in understanding isomerism, highlighting the importance of instructional strategies.